Fraction Multiplication: Analysis of Student Representation Errors Based on APOS Mental Mechanisms - Arifin, Samsul; Murniasih, Tatik Retno; Rahaju, Rahaju; Dani, Arik Varia (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
Most students find fraction material difficult because fractions are rarely encountered in life. Representing fractions in various forms is a problem for students. This research aims to reveal errors in the representation of multiplication of fractions by students at one of the junior high schools in Singosari. The researcher used a qualitative descriptive method with 32 students as potential subjects and 5 students were selected to be interviewed. Triangulation techniques are used by comparing test results, interviews and field notes. Research findings show that the two biggest errors occur in the representation of pictures and language. At the APOS mental mechanism stage, it was found that three out of five subjects made mistakes at the coordination stage. Further research is recommended to use media that can help students understand multiplication of fractions.